2018
DOI: 10.1007/s13361-018-1898-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sea Urchin Neuropeptide Landscape by Mass Spectrometry

Abstract: Neuropeptides are essential cell-to-cell signaling messengers and serve important regulatory roles in animals. Although remarkable progress has been made in peptide identification across the Metazoa, for some phyla such as Echinodermata, limited neuropeptides are known and even fewer have been verified on the protein level. We employed peptidomic approaches using bioinformatics and mass spectrometry (MS) to experimentally confirm 23 prohormones and to characterize a new prohormone in nervous system tissue from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The maturation and release of functional neuropeptides is regulated by several factors, among them the family of chromogranin/secretogranin proteins, which play a key role in the regulated secretory pathway ( 58 ). In this study we show the expression of Sp-SecV , previously identified in proteomic studies ( 25 ), specifically in the primary sensory neurons of the apical organ and in the pancreatic-like neurons of the lateral ganglia ( 52 ). Interestingly, human Secretogranin V (SGC5, Gene ID 6447) is specifically expressed in the brain, pancreas, adrenal and stomach, highlighting the conservation in deuterostomes of an ancient neuroendocrine molecular pathway.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The maturation and release of functional neuropeptides is regulated by several factors, among them the family of chromogranin/secretogranin proteins, which play a key role in the regulated secretory pathway ( 58 ). In this study we show the expression of Sp-SecV , previously identified in proteomic studies ( 25 ), specifically in the primary sensory neurons of the apical organ and in the pancreatic-like neurons of the lateral ganglia ( 52 ). Interestingly, human Secretogranin V (SGC5, Gene ID 6447) is specifically expressed in the brain, pancreas, adrenal and stomach, highlighting the conservation in deuterostomes of an ancient neuroendocrine molecular pathway.…”
Section: Discussionsupporting
confidence: 55%
“…Six additional putative NP genes were identified in S. purpuratus , in parallel with the discovery of homologs in other echinoderms (starfish Asterias rubens , brittle stars Ophionotus victoriae, Amphiura filiformis , and Ophiopsila aranea ) and also through phylogenomic studies ( 20 23 ). Mass spectrometry has also been used to determine the structures of some of the neuropeptides encoded by NP genes in S. purpuratus ( 16 , 18 , 24 , 25 ). Furthermore, characterization of neuropeptides and neuropeptide receptors in S. purpuratus and other echinoderms has provided important insights into the evolution of neuropeptide signaling.…”
Section: Introductionmentioning
confidence: 99%
“…First, a sequence-similarity search was performed against the crinoid proteomes using the amino acid sequences of already known neuropeptide precursors from several species of echinoderms as queries, including the brittle stars Ophionotus victoriae and Amphiura filiformis ( Zandawala et al, 2017 ), the starfish A. rubens ( Semmens et al, 2016 ) and Acanthaster planci ( Smith et al, 2017 ), the sea cucumber Apostichopus japonicus ( Chen et al, 2019 ) and the sea urchin S. purpuratus ( Rowe and Elphick, 2012 ; Monroe et al, 2018 ). BLASTP was conducted with high E-value threshold of 0.1 because neuropeptide precursors are relatively short (e.g., typically 50–150 residues) and often exhibit lower levels of interphyletic sequence similarity than other types of proteins ( Mirabeau and Joly, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Visualization of neuropeptide expression in echinoderm nervous systems was first enabled by use of antibodies to neuropeptides discovered in other phyla (e.g., the molluscan cardioactive peptide FMRFamide) ( Elphick et al, 1989 ; Garcia-Arraras et al, 1991 ; Hoekstra et al, 2012 ). More recently, insights into the neuropeptide repertoire of echinoderms were enabled by sequencing of the transcriptome/genome of the sea urchin Strongylocentrotus purpuratus (class Echinoidea) ( Burke et al, 2006 ; Rowe and Elphick, 2012 ; Monroe et al, 2018 ). Subsequently, analysis of transcriptome/genome sequence data has enabled discovery of neuropeptide precursor genes in other echinoderms, including sea cucumbers (class Holothuroidea), starfish (class Asteroidea), and brittle stars (class Ophiuroidea) ( Rowe et al, 2014 ; Semmens et al, 2016 ; Smith et al, 2017 ; Zandawala et al, 2017 ; Suwansa-Ard et al, 2018 ; Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of marine invertebrate neuropeptide systems have been revealed in Mollusca, annelids, marine arthropods (crustaceans) and echinoderms [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In echinoderms, the recent development of RNA high-throughout sequencing technology has allowed strong advances in the identification and characterization of neuropeptides in adults [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Neuropeptides in adult echinoderms have been proven to play important roles in muscle contractility, feeding and reproduction [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%